AN EMPIRICAL MODEL FOR THE ESTIMATION OF GLOBAL AND DIFFUSE SOLAR RADIATION OVER YOLA, NORTH-EASTERN NIGERIA BASED ON AIR TEMPERATURE - A, Alkasim,; A.B., Dikko,; E.S., Eyube, (IJRDO-Journal of Applied Science, 2017)
Accurate measurement of solar radiation distribution over any geographical location is desirable for the development of many solar thermal devices and their performance. A simple model for prediction of monthly mean daily solar radiation on a horizontal surface for Yola (longitude 10oE; latitude 9.23oN) was developed using a six (6) years data of daily maximum/minimum temperature records at the recently installed NECOP meteorological station in MAUTECH, Yola. The data was used to assess the applicability of global and diffused solar radiation. The clearness index, KT for the study period indicated that the solar radiation is available throughout thee year with a maximum value of 0.75 and minimum value of 0.66 indicating that solar appliance can work in Yola throughout the year. The regression constants a, b are 0.46, -0.82 respectively. The proposed model showed a very good agreement with the measured data with RMSE, MBE, and MPE values as 1.983 MJm-2 , -1.623 MJm-2 and 6.18% respectively